1998
DOI: 10.1104/pp.117.4.1401
|View full text |Cite
|
Sign up to set email alerts
|

The Boron Requirement and Cell Wall Properties of Growing and Stationary Suspension-CulturedChenopodium album L. Cells1

Abstract: Suspension-cultured Chenopodium album L. cells are capable of continuous, long-term growth on a boron-deficient medium. Compared with cultures grown with boron, these cultures contained more enlarged and detached cells, had increased turbidity due to the rupture of a small number of cells, and contained cells with an increased cell wall pore size. These characteristics were reversed by the addition of boric acid (>7 M) to the boron-deficient cells. C. album cells grown in the presence of 100 M boric acid enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 36 publications
5
61
0
5
Order By: Relevance
“…Application of PBA to bean caused root elongation even in the presence of boron and was used to propose that boron acting as a diester cross-linker has two effects on plant growth, both promoting root elongation and simultaneously stabilizing the cell wall and thereby inhibiting excessive elongation (Odhnoff, 1961). The latter is supported by Fleischer et al (1998), who showed that omission of boron from cultured Chenopodium cells in the stationary phase caused the cells to continue to expand and rupture. These data suggest that the stabilizing function of boron could be disrupted by boronic acids, which form monoester linkages and cannot replace the requirement for borate diester cross-links.…”
Section: Discussionmentioning
confidence: 97%
“…Application of PBA to bean caused root elongation even in the presence of boron and was used to propose that boron acting as a diester cross-linker has two effects on plant growth, both promoting root elongation and simultaneously stabilizing the cell wall and thereby inhibiting excessive elongation (Odhnoff, 1961). The latter is supported by Fleischer et al (1998), who showed that omission of boron from cultured Chenopodium cells in the stationary phase caused the cells to continue to expand and rupture. These data suggest that the stabilizing function of boron could be disrupted by boronic acids, which form monoester linkages and cannot replace the requirement for borate diester cross-links.…”
Section: Discussionmentioning
confidence: 97%
“…In future experiments, it will be useful to investigate whether the rol1 and lrx1 mutants change the pectin structure of root hairs and whether, for example, pore sizes might be affected in these lines. A method to measure porosity of pectin has been established for Chenopodium album (Fleischer et al, 1998) and can most likely be adapted for Arabidopsis to investigate this point. In a complementary approach, Fourier transform infrared spectroscopy (McCann and Carpita, 2005) might reveal changes in the molecular structure of cell walls of the different mutants.…”
Section: Rol1-1 and Rol1-2 Display Different Phenotypesmentioning
confidence: 99%
“…RG-II is the only known boratebinding polysaccharide in the primary cell wall, sequestering up to 80% of the cellular boron (B; Matoh et al, 1996). B deficiency results in altered plant growth and changes in cell wall architecture (Fleischer et al, 1998(Fleischer et al, , 1999Ishii et al, 2001). Thus, B-mediated cross-linking of RG-II generates a covalently crosslinked pectic network that is involved in the regulation of cell wall properties and plant growth (Fleischer et al, 1999;Ishii et al, 1999Ishii et al, , 2001.…”
mentioning
confidence: 99%